The indigenous young man with progressive abdominal distension - Wan Azfaruddin; Zamri Zuhdi; Affirul Chairil Ariffin; Azlanudin Azman; Firdaus Hayati; Razman Jarmin (Gazi Üniversitesi Rektörlüğü, 2018)
The incidence of pancreatic ascites is unusual. It is uncommon sequelae of chronic pancreatitis. Smith first discovered it in 1953 in the literature. The etiology includes chronic pancreatitis, pancreatic pseudocyst, pancreatic trauma and idiopathic in origin. Despite a rise in the incidence, it is scarcely reported. This is a case of a 20-year-old man presented with repeated acute pancreatitis episode complicated with gross ascites. Pancreatic duct stones were identified intra-operatively. Frey’s surgery was the procedure of choice. We discuss the presentation, choice of treatment and outcome.